PALM OIL STICK EXPORT MARKETING STRATEGY IN THE HINAI SUB-DISTRICT OF THE LANGKAT DISTRICT OF NORTH SUMATRA (CASE STUDY: UD. TEGAR PAMUNGKAS) - Putra, Rangga Hardiansyah (Syarif Hidayatullah State Islamic University Jakarta, 2024)
This study aims to identify the factors that are the strengths, weaknesses, opportunities, and threats to the export marketing of palm oil trunks and analyze the right strategies to be applied in marketing and increasing the fulfillment of oil palm trunk export needs. This research was conducted in Hinai District, Langkat Regency, North Sumatra. The data used in this study are primary and secondary. The data analysis methods used in this study are SWOT and QSPM analysis. The results of this study show that there are four alternative strategies, namely (SO1) increasing business facilities with available capital, (SO2) maintaining business consistency to meet market demand. (WO1) takes advantage of technological advances to obtain a wider market coverage, (WO2) makes all business supporting components so that the business continues to grow. (ST1) innovates product packaging to maintain quality, and (ST2) maintains supply to meet consumer needs. (WT1) conducts digital marketing to be better able to compete with similar industries. (WT2) adds equipment to minimize weather risks in meeting consumer needs. Based on the results of QSPM, the main strategic priority in this study is to improve business facilities with available capital.